ASSOCIATION OF LOW BACK PAIN AND SCIATICA WITH SIGNAL CHANGES IN THE VERTEBRAL ENDPLATE - GOTFRYD,ALBERTO OFENHEJM (2020)
ABSTRACT Objective To evaluate whether vertebral endplate signal changes (VESCs) influence the prognosis of patients submitted to conservative or surgical treatment for low back pain and lumbosciatica. Methods Study with 241 patients who underwent conservative treatment, infiltration or surgery with 12 months of follow-up. They were evaluated for pain by the Visual Analog Scale for Pain (VAS), for function by the Roland Morris questionnaire and for quality of life by the EuroQoI5 (EQ-5D). Results The VESCs did not have a significant effect on the treatment responses for the VAS (F = 0.03; P = 0.97), Roland Morris (F = 0.51; P = 0.60) and EQ-5D (F = 2.67; P = 0.07) variables, nor was there any interaction between VESC and treatment for VAS (F = 2.15; P = 0.08), Roland Morris (F = 1.55; P = 0.19) and EQ-5D (F = 2.15; P = 0.08). There was a significant effect for all treatments, however, the effect of the surgical procedure was superior when compared to the others (P <0.001). The VESC frequency was 48.33% for type 0, 29.17% for type I and 22.50% for type II. Conclusions The presence of VESC and its different types is not associated with a worse prognosis, nor was a higher prevalence of VESC observed in the patients with low back pain and lumbosciatica. Level of Evidence II; Retrospective cohort study.